Age-related effects on environmentally sustainable purchases at the time of COVID-19: Evidence from Italy. (May 2021) - Peluso, Alessandro M.; Pichierri, Marco; Pino, Giovanni
Abstract: The present research investigates whether the novel coronavirus disease (COVID-19) pandemic has modified consumers' spending on environmentally sustainable products by focusing on the role of age. An empirical study conducted in Italy during the first wave of the pandemic finds that consumers' age affected their reaction to the COVID-19 outbreak, and such age-related effects may have led to an increased propensity to spend on sustainable products. Indeed, the results show that consumers' age is inversely related to their negative affective reaction to the rise of contagion, which, in turn, is inversely related to their level of optimism experienced when the contagion slowed down due to public health interventions. Furthermore, this level of optimism is positively related to consumers' pro-environmental attitude and, thus, to their tendency to increase sustainable purchases. Graphical abstract: Image 1 Highlights: The current pandemic may increase consumers' spending on sustainable products. Consumers' age is inversely related to their negative affective reaction to the pandemic. Consumers' negative affect is inversely related to their optimism. Consumers' optimism is positively related to their pro-environmental attitude. This attitude increases consumers' tendency to spend on sustainable products.